1996
DOI: 10.1128/jb.178.13.3908-3916.1996
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a major cis-acting DNA element controlling the bidirectionally transcribed penicillin biosynthesis genes acvA (pcbAB) and ipnA (pcbC) of Aspergillus nidulans

Abstract: The ␤-lactam antibiotic penicillin is produced as a secondary metabolite by some filamentous fungi. In this study, the molecular regulation of the Aspergillus (Emericella) nidulans penicillin biosynthesis genes acvA (pcbAB) and ipnA (pcbC) was analyzed. acvA and ipnA are divergently oriented and separated by an intergenic region of 872 bp. Translational fusions of acvA and ipnA with the two Escherichia coli reporter genes lacZ and uidA enabled us to measure the regulation of both genes simultaneously. A moving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 55 publications
0
53
0
Order By: Relevance
“…After 24 h of cultivation, the coculture was prepared for HPLC analysis. For penicillin production, fermentation media were applied as previously described (39). Penicillin bioassay was carried out with Bacillus calidolactis C953 as an indicator organism (40).…”
Section: Methodsmentioning
confidence: 99%
“…After 24 h of cultivation, the coculture was prepared for HPLC analysis. For penicillin production, fermentation media were applied as previously described (39). Penicillin bioassay was carried out with Bacillus calidolactis C953 as an indicator organism (40).…”
Section: Methodsmentioning
confidence: 99%
“…The protein binding site identified here was nearly identical to that between acvA and ipnA which is bound by the putative regulatory protein PENRl (Then Bergh et al, 1996). Hence, cross-competition experiments were carried out using both the 50-base DNA fragment (WT) spanning the binding motif in the aat promoter, and a DNA fragment (AI) spanning the PENRl site between acvA and ipnA.…”
Section: Resultsmentioning
confidence: 97%
“…By means of band-shift analysis, a cis-acting DNA sequence containing a CCAAT core sequence was identified in the ant promoter which was specifically bound by a protein (complex). Partial purification of the binding protein and cross-competition experiments indicated that the identified CCAAT sequence was bound by the putative penicillinregulatory protein (complex) PENRI which was shown to bind to a similar CCAAT site between acvA and ipnA (Then Bergh et al, 1996). Mutation of the PENRI-binding site within the aat promoter led to a reduction of aat expression, providing evidence for the functionality of the PENRI-binding site in vivo.…”
mentioning
confidence: 98%
See 2 more Smart Citations